W cieniu mistrza. O etiudzie Stanisława Latałły Święta rodzina - Marek Hendrykowski (Images)
The text contains an analysis of Stanisław Latałło’s short film The Holy Family, shot at the ŁódźFilm School in the autumn of 1969. The author reconstructs the parabolic structure of this work and reveals the historical context of its realization, tied to the events of March 1968.